2019
DOI: 10.1002/mdc3.12728
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of the International Parkinson and Movement Disorder Society‐sponsored Non‐motor Rating Scale (MDS‐NMS)

Abstract: Background Non‐motor symptoms (NMS) are integral to Parkinson's disease (PD) and have a detrimental effect on patients and their caregivers. Clinical quantification has been aided by the development of comprehensive assessments such as the Non‐Motor Symptoms Questionnaire (NMSQuest) and Scale (NMSS). The NMSS has been widely used in clinical studies and trials; however, since its validation in 2007, our understanding of NMS has changed substantially. With the support of the International Parkinson and Movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 41 publications
0
30
0
1
Order By: Relevance
“…It, therefore, seems useful for patients suffering from dystonia, in addition to an assessment of motor symptoms, to carry out an assessment of the coexisting non-motor symptoms (depression, anxiety, cognitive impairment). A quick and clinically useful self-assessment, similar to the Movement Disorder Society Non-motor Scale (MDS-NMS) for Parkinson's disease (Martinez-Martin et al 2019b), was recently published for dystonia patients (Klingelhoefer et al 2019). Our results provide further evidence for the profound impact of dystonia on patients' HR-QoL.…”
Section: Hr-qol In Dystonia Patientsmentioning
confidence: 53%
“…It, therefore, seems useful for patients suffering from dystonia, in addition to an assessment of motor symptoms, to carry out an assessment of the coexisting non-motor symptoms (depression, anxiety, cognitive impairment). A quick and clinically useful self-assessment, similar to the Movement Disorder Society Non-motor Scale (MDS-NMS) for Parkinson's disease (Martinez-Martin et al 2019b), was recently published for dystonia patients (Klingelhoefer et al 2019). Our results provide further evidence for the profound impact of dystonia on patients' HR-QoL.…”
Section: Hr-qol In Dystonia Patientsmentioning
confidence: 53%
“…1. MDS‐NMS (see Appendix): After the pilot study, the final version of the MDS‐NMS has 52 items, grouped according to clinical content into 13 domains: (1) depression (5 items), (2) anxiety (4 items), (3) apathy (3 items), (4) psychosis (4 items), (5) impulse control and related disorders (4 items), (5) cognition (6 items), (7) orthostatic hypotension (2 items), (8) urinary (3 items), (9) sexual (2 items), (10) gastrointestinal (4 items), (11) sSleep and wakefulness (6 items), (12) pain (4 items), and (13) other (5 items; unintentional weight loss, decreased smell, physical fatigue, mental fatigue, and excessive sweating). Items are scored for frequency (from 0 [never] to 4 [majority of time]) and severity (from 0 [not present] to 4 [severe]), which are multiplied to generate the item total score.…”
Section: Methodsmentioning
confidence: 99%
“…The issues listed above led to the development and validation of a new, updated rater‐administered scale, the IPMDS Nonmotor Rating Scale (MDS‐NMS), based on the NMSS and supported by the IPMDS. Data on acceptability and reliability of the preliminary version of the MDS‐NMS in a study population of neurologists, PD patients and healthy controls as part of a cognitive pretesting study have been reported . Here we report the clinimetric properties of the MDS‐NMS from a formal validation study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both are suitable for detecting prevalence of NMS within PD populations [51] and have been used as secondary outcomes in PD trials. The MDS-NMS has recently been published [52].…”
Section: Non-motor Symptomsmentioning
confidence: 99%